Peace Agreement For Bad Credit Cases Between Banks And Debtors Using Notary Services - Hafid Arisanto, Muhammd (International Significance of Notary, 2025)
Abstract: Notaries have a very important role in helping to create legal certainty and protection for the community. The Law on Notary Positions and the Notary Code of Ethics do not expressly prohibit Notaries from entering into agreements with any parties. The problem formulation for this thesis is how to arrange a debtor's peace agreement with the bank using the services of a notary and the contents of the peace deed and what if problems arise between the debtor and the bank. In writing this thesis, normative legal research or doctrinal legal research is used. Normative research is a type of research used by researchers to prepare this thesis. This thesis uses normative juridical research methods, through a statutory approach, a concept approach and a case approach The first result of this research is that the rules for a peace agreement between a bank and a debtor using the services of a notary are contained in the law, and secondly, the contents of what the parties do in resolving a dispute can be done with the help of a notary. Arrangements for peace agreements between banks and debtors in bad credit cases using notary services are contained in many laws. And the point is that delays in payments or bad credit can occur due to several factors, that's why this arrangement is made so that the parties don't feel at a disadvantage, and can also protect the parties from mistakes in the agreement. The form or content of the peace agreement between the bank and the debtor in the event of bad credit can be adjusted to the interests of the disputing parties, and the notary in this case is only a mediator or arbitrator.